Conceptions of instruction in the workplace - Jane E. Beno (Adult Education Research Conference, 1994)
om interviews of twenty-two workplace instructors of adults, three conceptions of instruction emerged: imparting information to learners (Transmission Conception); assisting learners to share ideas and experiences (Enablement Conception); involving learners in the construction of meaning (Constructive Conception). These findings have implications for training instructors of adults and evaluating instruction.